2019
DOI: 10.3897/pharmacia.66.e38573
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester (CAPE): pharmacodynamics and potential for therapeutic application

Abstract: Caffeic acid phenethyl ester (CAPE) is the major pharmacologically-active component of some propolis types, rich in polyphenols, such as poplar propolis types. CAPE has the potential to be applied as a pharmaceutical as it possesses most of the pharmacological activities of propolis, such as anti-proliferative, antioxidant, immunomodulatory, antidiabetic, anti-inflammatory and antimicrobial. Its advantage is that it lacks some of the downsides of total propolis extracts, such as inability for unified standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Chen et al reported that CAPE attenuated the expressions of Bcl-2, Bcl-2, and caspase-3 in leukemia cell lines, which subsequently led to cell death [ 178 ]. Yordanov et al also showed that CAPE exhibits antioxidant effects on murine skin at lower doses [ 179 ]. In short, CAPE may act as a chemopreventive agent for skin cancer, however, clinical trials are required to verify the overall efficacy.…”
Section: Dietary Phytochemicals For Skin Cancer Therapymentioning
confidence: 99%
“…Chen et al reported that CAPE attenuated the expressions of Bcl-2, Bcl-2, and caspase-3 in leukemia cell lines, which subsequently led to cell death [ 178 ]. Yordanov et al also showed that CAPE exhibits antioxidant effects on murine skin at lower doses [ 179 ]. In short, CAPE may act as a chemopreventive agent for skin cancer, however, clinical trials are required to verify the overall efficacy.…”
Section: Dietary Phytochemicals For Skin Cancer Therapymentioning
confidence: 99%
“…This first period is followed by one of rapidly increasing number of publications, predominantly elucidating the mechanisms behind CAPE's pharmacological activities and proposing new applications for diseases, known to be affected by these activities. This period after the year 2000 and especially the research on the basic principles behind CAPE's impressive diversity of biological effects are the subjects of a related article (Yordanov 2019). Table 1 presents chronologically cornerstone publications on CAPE research, clearly demonstrating its plethora of pharmacological activities.…”
Section: Discovery and Cornerstone In Vitro And In Vivo Studiesmentioning
confidence: 99%
“…It can be easily synthesized, having a relatively simple structure, resolving the characterization and standardization issues. An overview on the potential of CAPE for therapeutic application, focusing on the pharmacodynamic principles, underlying its various pharmacological activities, as well as registered clinical trials has been presented in a related article (Yordanov 2019). The current review is focused on the discovery of CAPE and its pharmacological potential as well as practical approaches for its pharmaceutical formulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been studied extensively as the most important individual component of propolis. Existing studies focused on its potential therapeutic properties such as its antibiotic, antioxidant, anti-inflammatory, anti-oxidative stress, antitumor, antidiabetic, anti-neurodegeneration, and anti-anxiety properties [ 13 , 16 , 17 ]. Numerous studies demonstrated the antibacterial activity of CAPE against different bacterial species [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…CAPE may be a promising natural product for clinical application in the future [ 21 ]. One of the major advantages is that CAPE is devoid of some negative aspects of crude extracts of propolis, which includes, the inability to be standardized, which is a keystone of implementing it as therapy in the field of medicine [ 16 ]. This study aimed to investigate how CAPE, as a single molecule, affects planktonic growth, biofilm-forming abilities, mature biofilms, and cell death of some Candida albicans and non-albicans Candida species and strains.…”
Section: Introductionmentioning
confidence: 99%